The Effectiveness of the Shredder Machine and Empty Fruit Bunch Press to Reduce Oil Losses from Oil Palm Empty Fruit Bunches - Sahrial Hafids; Dewi Fortuna; Ade Rizka Wahyuni (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2018)
The purpose of this study was to determine the effectiveness of the use of